The problems of teaching Arabic Rhetoric for the secondary grade students in Jordan from teachers’ point of view and its relationship with the gender and teaching experience - Saadah, Fayza Ahmed (Journal of Educational and Psychological Sciences, 2021)
The study aimed at identifying the problems of teaching Arabic Rhetoric for the secondary grade students in Jordan from teachers’ point of view. using the descriptive analytical curriculum, the sample of the study consisted of (85) secondary classroom teachers of Arabic language in the Directorate of the University directorates to answer the questionnaire, they are the whole study community. And (16) teachers to answer the corresponding questions. Data was analyzed by using (SPSS) to find means, ranks, and the level. And "t" test. The results of the study showed that the level of the rhetoric teaching problems facing the secondary grade students in university directorates from teachers’ point of view was moderate as a whole, with a mean of (2.80). Moreover, teaching problems related to the dimensions of the required (textbook) was in the first place, with a high level. Whereas, the level of the rhetoric teaching problems related to (the teacher dimension) was low with the lowest means. This study also shows that There were no significant statistical differences due to gender and teaching experience meanwhile the results showed no statistically significant differences for the interaction between gender. And accordingly, a set of recommendations and suggestions were presented to solve the problem of rhetoric teaching to the secondary students and support teaching it.